IMPLEMENTASI METODE READING ALOUD UNTUK MENGEMBANGKAN KETERAMPILAN BERBAHASA ANAK USIA DINI 5-6 TAHUN DI KELAS B TK NEGERI 2 MANDASTANA - Lestari, Suci; Nisa, Uswatun; Zulkarnaen, Muhammad; Baiti, Noor (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of developing early childhood language skills as a foundation for communication development and learning readiness. A preliminary study in Class B at TK Negeri 2 Mandastana revealed that some children lacked focus while listening to stories, hesitated to express their opinions, and faced difficulties in retelling story content. This study aims to describe the implementation of the